Advances in nonequilibrium molecular dynamics simulations of lubricants and additives - J. P. Ewen; D. M. Heyes; D. Dini (Friction)
Abstract Nonequilibrium molecular dynamics (NEMD) simulations have provided unique insights into the nanoscale behaviour of lubricants under shear. This review discusses the early history of NEMD and its progression from a tool to corroborate theories of the liquid state, to an instrument that can directly evaluate important fluid properties, towards a potential design tool in tribology. The key methodological advances which have allowed this evolution are also highlighted. This is followed by a summary of bulk and confined NEMD simulations of liquid lubricants and lubricant additives, as they have progressed from simple atomic fluids to ever more complex, realistic molecules. The future outlook of NEMD in tribology, including the inclusion of chemical reactivity for additives, and coupling to continuum methods for large systems, is also briefly discussed.